Potential Infused Water with a Combination of Ginger, Turmeric, Galangal, Lemongrass, Lime and Honey Pure: a Literature Review Activities Antioxidants and Functional - Fidanli, Sekha Seylana; Pirmansah, Tedi; Putri, Khalisa Halima; Zuraida, Maila; Falah, Tata Agustin Nurul; Zahra, Shorea Jasmine Az; Firdaus, Azka Zulfahnur; Febriyanti, Asniar Rizka; Pamungkas, Wisnu Putra; Banowati, Annisa Tri; Pangestu, Ardi Ma’ruf Dwi; Aziz, Rama Nur; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Infused water is water that is given additional fruits, spices or vegetables and left for a few hours or overnight in the refrigerator, so that the water gives taste and is beneficial for health. The goal of this process is to help the body cope with metabolic residues and toxins that can cause strain, indigestion, and chemical exposure from the environment. This systematic review was conducted by collecting research data from four major internationally recognised scientific databases to ensure the comprehensiveness and credibility of the literature analysed. Databases used include PubMed as the largest biomedical database maintained by the National Center for Biotechnology Information (NCBI), ScienceDirect as Elsevier's full-text scientific article access platform, Google Scholar to cover gray literature and open-access publications that may not be indexed in commercial databases, and ResearchGate as an academic platform that provides access to preprints and the latest publications from researchers around the world. The purpose of this infusion water formula is to provide benefits that go beyond sensory perception and include real physical benefits. The results of the study show that the combination of these substances has good synergy in increasing toxin excretion, increasing hydration, and improving the body's metabolism. Therefore, this drink has the potential to be developed into a functional drink based on natural ingredients that is safe and easy to make, which supports overall health. This work is licensed under a Creative Commons Attribution 4.0 International License.